Globalization and labour relations - Leisink, Peter (Cheltenham, UK ; Northampton, Ma. : E. Elgar, 1999)
This book presents an in-depth analysis of the neo-liberal viewpoint on globalization and its impact on labour relations. The policies of states and multinational corporations as well as their effects are analysed from the perspectives of international political economy, institutional economics, cultural studies and industrial relations.
Includes bibliographical references and index.
osc 31/08/16; opc 07/09/16
Loans
Keywords: Industrial relations; Foreign trade and employment